Analysis the Role of Management for Achieving of Public Health Coverage Programs at Public Health Care in Bengkulu - Syaiful Anwar Ab1 , Henni Febriawati1,2, Lizar Alfansi1 , Efffed Darta Hadi1 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: Public Health Care is a primary public health service center. It is also as a promotive and preventive service provider with a target group and community to maintain and improve health and prevent disease. In the implementation of the health program the management function in the public health center is called planning (P), Mobilizing implementation (MI), Supervision Control Assessment (SCA). The purpose of conducting a public health care management analysis is Planning (P), Mobilizing Implementation (M.I), and Supervision Control Assessment (SCA) on the achievement of public health care performance indicators in Bengkulu City. Study Design: The research design used is exploratory or non-experinmental research for qualitative methods and analytic research designs are cross sectional observational approaches for quantitative methods with hypothesis testing. Informants in this qualitative study were carried out by means of purposive sampling, namely by conducting interviews with all the Head of Public Health Center. The sample in this study amounted to 80 samples consisting of the head of the Public Health Center, the person in charge of the program and the implementer of the Public health care program/activity Results: There is a relationship between Management functions (planning, mobilizing implementation, controlling assessment control) to the achievement of the performance of the Environmental Health, Nutrition, Prevention and Disease Control program at Bengkulu City Health Center; Conclusion: The implementation of management functions (Planning, Mobilizing Implementation, Supervision Control Assessment) influences the Environmental Health, Nutrition, Disease Prevention and Control program in Bengkulu City Health center.